England’s Abberley-Malvern Hills Geopark as a Tourism Project - Mazurski, Krzysztof R. (Geotourism/Geoturystyka, 2013)
The welfare initiative has led to a creation of Abberley-Malvern Hills Geopark in the borderland of West England and Wales. It covers places of a very long geological profi le with many geosites. They are a base for a development of tourism and educational activity. It resulted in many entertainments, meetings and publications as well as new elements of tourist management, of course. Many solutions can be used for a work of Polish geoparks.